Atmospherically induced defects in (FASnI3)0.6(MAPbI3−3xCl3x)0.4 perovskites. (22nd February 2019) - Junda, Maxwell M; Zhao, Dewei; Subedi, Biwas; Wang, Changlei; Chen, Cong; Yan, Yanfa; Podraza, Nikolas J
Abstract: The effects of brief atmospheric exposure are assessed for mixed composition perovskites comprised of a combination of formamidinium tin iodide (FASnI3 ) and methylammonium lead iodide  +  chloride (MAPbI3−3 x Cl3 x ) as well as MA0.7 FA0.3 PbI3 perovskite for use as absorber layers in high-efficiency thin film solar cells. Photothermal deflection spectroscopy (PDS) is employed to probe the relative defect density of all films by way of extracting the Urbach energy characterizing the width of the sub-bandgap absorption tail. Exposure to atmosphere for ~3 min prior to PDS measurement is found to degrade mixed composition films such that exposed films had an average increase of 36% in Urbach energies compared to those that are fully kept out of atmosphere through immersion in inert C6 F14 liquid. By contrast, the same exposure to atmosphere induced no change in Urbach energy for MA0.7 FA0.3 PbI3 . These results demonstrate the influence of ambient exposure on perovskites, particularly those containing Sn, and highlight the fact that handling procedure itself throughout all fabrication and subsequent characterization steps influences the measured results.